KEGUNAAN NASKAH AKADEMIK DALAM PROSES PENYUSUNAN RANCANGAN UNDANG-UNDANG - , Ismet Hadi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to understand political law the formation of legislation, determine academic paper settings in the formation of legislation, and know the urgency of academic paper in the formation of legislation. This research is a normative juridical law which uses the method of analysis perspective. Most of the data obtained through library research conducted by examining library materials such as books, journals, research reports and/or other secondary data were then analyzed descriptively.. The results of this study, First, the political law as a general framework that will shape the law in an effort to realize the ius constituendum. legal political legislation before the constitutional amendment in 1945 highly dependent on the President, where the President has the power to make laws while the House of Representatives just as a place to seek approval or withhold in the discussion of draft legislation, but it was changed after the 1945 Constitution amended a shift in the power of the lawmakers who originally vested in the President shifted into the power of the Board of Representatives. Second, the existence of an academic paper in any draft legislation can provide a picture of the results of scientific research that underlies the proposal draft any legislation that will be presented and discussed in the House of Representatives, with an academic paper then give a free society aspirations as well as to appreciate the substance of the draft legislation that will be and are being regulated. Third, urgency academic paper is one form of embodiment of the principles of the formation of legislation that either an attempt to explain in more open to all stakeholders about the significance of the presence of a legislation.. Key Words: Political of Law, Establishment of Act, Academic Paper